Spinoza and Republicanism - Prokhovnik, R. author. aut Link
IX, 280 p.
Keywords: Dutch republicanism represents a crucially important context within which to discuss Spinoza's political theory and his conception of politics. Spinoza and Republicanism provides an important account of his key political concepts, as well as a fresh and stimulating perspective on the links between Spinoza's two political works and contemporaneous debate and traditions. By identifying the distinctiveness of Dutch republicanism and Spinoza's contribution to it, Raia Prokhovnik also throws new light on recent discussions of republicanism and its history.